Biomimetic Ca-P coatings Incorporating bisphosphonates produced on starch-based degradable biomaterials - Oliveira, A. L. (2010)
In this study, sodium clodronate, a well-known therapeutic agent from the family of bisphosphonates (BPs), is incorporated in a biomimetic calcium phosphate (CaP) coating, previously formed on the surface of a starch-based biomaterial by a sodium silicate methodology, as a strategy to develop a site-specific drug delivery system for bone tissue regeneration applications. The effects on the resulting CaP coatings were evaluated in terms of morphology, chemistry, and structure. The dissolution of Ca and P from the coating and the release profiles of sodium clodronate was also assessed. As a preliminary approach, this first study also aimed at evaluating the effects of this BP on the viability of a human osteoblastic cell line since there is still little information available on the interaction between BPs and this type of cells. Sodium clodronate was successfully incorporated, at different doses, in the structure of a biomimetic CaP layer previously formed by a sodium silicate process. This type of BPs had a stimulatory effect on osteoblastic activity, particularly at the specific concentration of 0.32 mg/mL. It is foreseen that these coatings can, for instances, be produced on the surface of degradable polymers and then used for regulating the equilibrium on osteoblastic/osteoclastic activity, leading to a controlled regenerative effect at the interface between the biomaterial and bone.